2011
DOI: 10.1097/olq.0b013e318214bb70
|View full text |Cite
|
Sign up to set email alerts
|

Correlates of HIV Testing History Among Urban Youth Recruited Through Venue-Based Testing in 15 US Cities

Abstract: Background Adolescents and young adults comprise disproportionately high percentages of individuals living with HIV and those with undiagnosed HIV. Our objective was to determine factors associated with history of HIV testing and receipt of results among a sample of urban, high-risk, sexually active adolescents in 15 U.S. cities. Methods 20–30 sexually active youth, aged 12–24 years, were recruited to participate in an anonymous survey and HIV antibody testing at 2–3 venues per city identified by young men w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
20
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 18 publications
(22 reference statements)
3
20
0
Order By: Relevance
“…18 Demographic factors suggest that among adolescents and young adults, HIV testing is higher among females, 18,19 African American, 7,8,[18][19][20][21][22][23] and Latino/a 19,20,24 youth. Sexual factors associated with increased HIV testing among youth include having three or more sexual partners in the last three months, 21 ever having a sexually transmitted infection (STI), 21,25 inconsistent condom use, 21 substance use, 21 being a MSM or a female who had sex with a MSM, 7,8,19,[21][22][23][24] or having had sex with an HIV-infected partner. 21 Healthcarerelated factors associated with increased HIV testing among youth include those receiving Medicaid with a primary care physician who were recommended testing 20 or had any healthcare in the past year.…”
Section: Hiv Testing Among Adolescentsmentioning
confidence: 99%
See 2 more Smart Citations
“…18 Demographic factors suggest that among adolescents and young adults, HIV testing is higher among females, 18,19 African American, 7,8,[18][19][20][21][22][23] and Latino/a 19,20,24 youth. Sexual factors associated with increased HIV testing among youth include having three or more sexual partners in the last three months, 21 ever having a sexually transmitted infection (STI), 21,25 inconsistent condom use, 21 substance use, 21 being a MSM or a female who had sex with a MSM, 7,8,19,[21][22][23][24] or having had sex with an HIV-infected partner. 21 Healthcarerelated factors associated with increased HIV testing among youth include those receiving Medicaid with a primary care physician who were recommended testing 20 or had any healthcare in the past year.…”
Section: Hiv Testing Among Adolescentsmentioning
confidence: 99%
“…Sexual factors associated with increased HIV testing among youth include having three or more sexual partners in the last three months, 21 ever having a sexually transmitted infection (STI), 21,25 inconsistent condom use, 21 substance use, 21 being a MSM or a female who had sex with a MSM, 7,8,19,[21][22][23][24] or having had sex with an HIV-infected partner. 21 Healthcarerelated factors associated with increased HIV testing among youth include those receiving Medicaid with a primary care physician who were recommended testing 20 or had any healthcare in the past year. 21 A study of high-risk Latino and African American gang members in Los Angeles found that only 33% had prior HIV testing.…”
Section: Hiv Testing Among Adolescentsmentioning
confidence: 99%
See 1 more Smart Citation
“…The questionnaire was constructed by the researchers and included variables derived from instruments previously validated in vulnerable populations (10,11,24,26,27,30,(32)(33)(34)(35)(36)(37)(38)(39) and other potential factors associated with HIV testing. The interviews were conducted by members of the study team who were professional experts in mental health and had been previously trained.…”
Section: Discussionmentioning
confidence: 99%
“…Findings on ethnic/racially diverse samples of adolescents suggest predictors of testing include sexual experience, high risk sexual behaviors, experience with same-gender partner, HIV-related partner communication, substance use, prior sexually transmitted infections testing, access to free testing services, availability of rapid testing methods, and confidential results [6][7][8][9][10]. To date, little is known about HIV testing among Hispanic adolescents despite the serious threat of HIV infection in the Hispanic community.…”
Section: Introductionmentioning
confidence: 99%